2022
DOI: 10.1038/s41598-022-23954-8
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of extracellular DNA associates with treatment response in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) as a chronic autoimmune inflammatory disease increases extracellular DNA (ecDNA). Our previous study has shown that anti-inflammatory treatment reduces ecDNA, but it is unclear whether there is an association with treatment response. The aim of this study was to analyze the changes of ecDNA induced by biological disease-modifying antirheumatic drugs (bDMARDs) in RA patients with an emphasis on the subcellular origin of ecDNA. Plasma samples from 40 RA patients were collected in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In systemic lupus erythematosus (SLE), impaired degradation of extracellular DNA by deoxyribonuclease (DNase) 1 was shown to contribute to the upregulation of mtDNA in the plasma of some patients [ 42 , 43 ]. The one study investigating the activity of DNase1 in RA, however, did not find an impairment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In systemic lupus erythematosus (SLE), impaired degradation of extracellular DNA by deoxyribonuclease (DNase) 1 was shown to contribute to the upregulation of mtDNA in the plasma of some patients [ 42 , 43 ]. The one study investigating the activity of DNase1 in RA, however, did not find an impairment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that the latter lack of significance results from the high number of patients in remission and the small number of patients with high activity in our study. Other investigators have suggested a significant correlation between elevated plasma cfDNA levels and DAS28 [6,44]. It must be determined in further studies, if mtDNA quantification has a potential in the monitoring of longitudinal changes in RA activity, as demonstrated for SLE [32] and anti-citrullinated protein antibodies (ANCA)-associated vasculitis [45].…”
Section: Discussionmentioning
confidence: 99%
“…We have described how the application of the biological treatment led to a decrease in thiobarbituric acid-reacting substances as a marker of lipid peroxidation [6]. We have also observed a decrease in extracellular DNA, which can cause a decrease in inflammation or be its consequence [24][25][26]. Given that RA also causes cartilage and bone damage that ultimately has a major effect on quality of life, the administration of anti-TNF also leads to functional benefits such as cartilage remodeling and periodontal status, as RA and periodontitis share similarities in the pathomechanism of the disease, like the production of interleukins [27,28].…”
Section: Introductionmentioning
confidence: 91%